Assombro de olhada de bicho: uma etnografia das concepções e ações em saúde entre ribeirinhos do baixo rio Tapajós, Pará - Brasil - Wawzyniak, João Valentin (Universidade Federal de São Carlos, 2008)
This ethnography has as an objective to comprehend the logic in which the riverside population from the low river Tapajós, Pará State, Brazil, conceive the diseases and the treatments facing the Public Health programs which seek to orient these conceptions according to an own logic, and also how they answer to that according to their cosmological system. The central question consists on knowing how they acquire the biomedical speech, the clinical practice, and the public policies in Health and associate them to their therapeutic traditional model. The ethnographic material described and analyzed here was obtained during a field research (participant observation and interviews), carried out in three periods, between 2005 and 2007, in the communities Prainha do Tapajós, Prainha, Taquara, Itapaiuna and Paraíso situated in the perimeter of a federal conservation unit, and in Santarém and Belterra cities. It is noted that the riverside population acquire the outside agents and proposed changes according to pre-existing cultural schemes and articulate the biomedical model procedures with the therapeutic traditional model, as they do not see incongruence between them, even with some tension points. The Cure local specialists and the health community agents are found as fundamental subjects of this articulation and of the therapeutic itinerary.
Keywords: Antropologia da saúde; Amazônia; Medicina alternativa; População rural; Xamanismo; Saúde pública; Ribeirinhos; Rio Tapajós; Modelos terapêuticos; Amazon; Riverside population; Tapajós river; Therapeutic models; Health; Anthropology; CIENCIAS HUMANAS::SOCIOLOGIA